Discursos sobre moradia no jornalismo on-line: valoração, apagamento e reenunciação discursiva - Padilha, Paula Caroline Zarth (2019)
The present research sought to understand the discourses about the right to housing, produced in news and reportages of online journalism. The epistemological anchoring contemplates the theoretical elaboration of the Bakhtin Circle (BAKHTIN, 1993 [1965]; BAKHTIN, 2008 [1961]; BAKHTIN, 2010 [1920]; BAKHTIN, 2015 [1930]; BAKHTIN, 2016 [1978]; MEDVIÉDEV, 2012 [1928]; VOLÓCHINOV, 2017 [1929]; VOLOCHÍNOV, 2013 [1930]) and contemporaneous commentators (ACOSTA PEREIRA, 2013; BEZERRA, 2015; BRAIT, 2007; FARACO, 2009; GRILLO, 2017; RODRIGUES, 2005; ROHLING, 2014). Data consists of enunciative chains, having as the triggering event the Fearless People Occupation, in São Bernardo do Campo (São Paulo), which took place from September 2017 to April 2018. The enunciative chains, object of this study, were analyzed as of the concepts of enunciation, dialogism, sign and appreciative/evaluative horizon, considering their circulation around the journalistic sphere. For data cut, content produced on the news websites G1, Veja.com and Rede Brasil Atual were selected, as well as the respective online comments from readers. To set up the great temporality of the discourses related to the mobilization for housing, we trigger a history delineated by Rolnik (2015), Harvey (2012) and Engels (2015 [1872]). Furthermore, the present study theoretically and methodologically mobilizes the Dialogical Analysis of Discourse (DAD) to observe and analyze the prominent discursive recurrences in the enunciative chains of news, reportages and online comments that set the evaluative horizon about the thematic and the social subjects involved, mediated by the new technologies used by journalism in online platforms. In this discursive context, the digital technologies allow the amplification of the re-accentuation of news throughout online comments. In order to discuss the aspects related to the Social Communication field, more specifically to journalism, we used the theory of Genro Filho (2012), Habermas (2014) and Schwingel (2012). Acting as the more prominently recurrences that emerged from data, we noticed that: 1) the understanding of housing as property appears in a more remarkable way in the media, especially the hegemonic one; 2) the chronotope of discourses of housing as a right is pointed by the media that makes the counter-narrative; 3) the reader-commenters deprecatingly enunciate themselves egarding the mobilization and the occupation subjects; 4) from the noticed recurrences, the present research identified in the data a process of erasure and invisibilization of the mobilization for housing. It also surfaces the tangibility of the debate around housing. Of the two chronotopes of discourse on housing analyzed, the first being understood as property and the second as a right, other objects of discourse are presented by the media and re-communicated by commenters: the criminalization and marginalization of the homeless subject and the emphasis of the stories in renowned social actors are the conspicuous of this different appreciative horizon on the Fearless People Occupation. The homeless subject’s identity construction is therefore given by the heterodiscursive relations with readers/commenters, from the production of news and reportages: the subject is referenced as a wanderer, an invasor, someone who doesn’t want to pay for dwelling. A counter-narrative also presents itself as a discursive reaffirmation about itself, of a working homeless subject who is unemployed and seeks in the occupation a viable financial option to live.